MIGRANT WORKERS' REMITTANCES AND OUTPUT GROWTH IN SUB-SAHARAN AFRICAN COUNTRIES - Henry Okodua (European Scientific Journal, ESJ, 2012)
Economic growth and development processes affect and are affected by migration of people. While migration of skilled workers could potentially hurt the sending economies due tooutright deprivation of vital human resources,the migrant sending countries of Africa can also benefit economically from migration through the inflow of workers‟ remittances.This study sheds new light on this relationship by examining the economic growth outcomes of workers‟ remittance flows to some selected Sub-Saharan African countries. The hypothesized link between workers‟ remittances and output growth was specified in alinear dynamic panel data model and estimated using the system Generalized Method of Moments. The study found a negative and statistically insignificant link between remittancesand output growth across the sampled countries over the study period. This result suggests that workers‟ remittances may not be relied upon for now to promote economic growth in the SSA region.